The Effect of Concrete Compressive Strength Using Suralaya Power Plant Fly Ash and Alkali Activator - Gita Amanda Yulianti; Wahyu Kartini; Nia Dwi Puspitasari (Racic : Rab Construction Research, 2026)
The Suralaya Power Plant produces approximately 700,000 tons of fly ash and bottom ash annually. To manage this waste, fly ash can be incorporated into concrete mixtures. Fly ash contains silica and alumina, which can react with calcium hydroxide (Ca(OH)₂), a byproduct of cement hydration. When activated with an alkaline solution of NaOH and Na₂SiO₃, fly ash can exhibit binding properties. In this study, specimens were prepared using Class F fly ash sourced from the Suralaya Power Plant in proportions of 0%, 100%, 90%, and 80%, activated with an alkaline solution at a ratio of 1:2.5 (10 M NaOH:Na₂SiO₃), and tested at 28 days with water cement ratios (w/c) of 0.45 and 0.55. Class F fly ash was chosen due to its slower setting time compared to Class C. The objective was to evaluate the compressive strength of concrete with varying fly ash percentages and alkaline activators. Results show that fly ash concrete with an alkaline activator (1:2.5) had high slump but low workability due to high viscosity. For w/c 0.45, 100% fly ash increased compressive strength by 58.72% compared to 100% cement concrete. For w/c 0.55, 100% fly ash achieved the highest increase, at 141.03% over 100% cement concrete.